Ablation of the Cβ2 subunit of PKA in immune cells leads to increased susceptibility to systemic inflammation in mice. Issue 11 (14th September 2017) - Moen, Line Victoria; Sener, Zeynep; Volchenkov, Roman; Svarstad, Anja Camilla; Eriksen, Aud Marit; Holen, Halvor L.; Skålhegg, Bjørn S.
Abstract: Protein kinase A (PKA) is a holoenzyme composed of a regulatory subunit dimer and two catalytic subunits and regulates numerous cellular functions including immune cell activity. There are two major catalytic subunit genes, PRKACA and PRKACB encoding the catalytic subunits Cα and Cβ. The PRKACB gene encodes several splice variants including Cβ2, which is enriched in T‐, B‐ and natural killer cells. Cβ2 is significantly larger (46 kDa) than any other C splice variant. In this study we characterized mice ablated for the Cβ2 protein demonstrating a significantly reduced cAMP‐induced catalytic activity of PKA in the spleenocytes, lymphocytes and thymocytes. We also observed a significantly increased number of CD62L‐expressing CD4 + and CD8 + T cells in LNs, accompanied by increased susceptibility to systemic inflammation by the Cβ2 ablated mice. The latter was reflected in an elevated sensitivity to collagen‐induced arthritis (CIA), as well as higher concentration of TNF‐α and lower concentration of IL‐10 in response to LPS challenges. We suggest a role of Cβ2 in regulating innate as well as adaptive immune sensitivity in vivo. Abstract : Lymphocytes express three different forms of the catalytic subunit of PKA called Calpha1, Cbeta1 and Cbeta2. Whereas Calpha1 regulates lymphocyte proliferation the role of Cbeta in lymphocytes is enigmatic. We show that mice lacking Cbeta2 are hypersensitive to inflammation suggesting that Cbeta2 regulates immune sensitivity to foreign substances.